A Rat's Whiskers Point the Way toward a Novel Stimulus-Dependent, Protective Stroke Therapy. (June 2013) - Frostig, Ron D.; Lay, Christopher C.; Davis, Melissa F.
Stroke is the fourth leading cause of death in the United States and the leading cause of long-term disability. Ischemic stroke, due to an interruption in blood supply, is particularly prevalent; 87% of all strokes are ischemic. Unfortunately, current options for acute treatment are extremely limited and there is a great need for new treatment strategies. This review will discuss evidence that mild sensory stimulation can completely protect the jeopardized brain from an impending stroke in a rodent model. When delivered within the first 2 hours following ischemic onset, this stimulation results in complete protection, including a full reestablishment of cortical function, sensorimotor capabilities, and blood flow. Identical stimulation, however, initiated 3 hours following ischemic onset, results in an increase in damage compared with untreated animals. The protective effect is not specific to a single sensory modality, anesthesia, or age, and increasing evoked cortical activity by increasing stimulation accelerates recovery. Taken together, these findings demonstrate that cortical activity is a critical factor for protection and suggest a new, exciting potential avenue for the development of acute stroke treatment strategies that may produce a noninvasive, drug-free, equipment-free, and side effect–free means of protecting from ischemic stroke.